Hubungan Antara Persepsi Terhadap Iklim Organisasi Dengan Perencanaan Karir Pada Guru Di SMAN 1 Sewon - Mandara, Dicky (EMPATHY Jurnal Fakultas Psikologi, 2013)
ABSTRACTThis study aims to examine the relationship between perceptions of organizational climate with career planning on the teacher. Subjects that was used in this study are 62 teachers from senior high school Sewon. The scale of organizational climate and career planning scale was used to collect the data. The method of data analysis in this study used Pearson product moment correlation with SPSS 15 for windows sofware. The results of the data analysis found that the correlation between the organizational climate with career planning is significant with rxy = 0.471 and p = 0.007. R squared values between the organizational climate and career planning is 0.222 or 22.2%. This may implied that the variables can explain the variable Organizational Climate Career Planning of 22.2% while the rest (77.8%) is explained by other variables. Level of organizational climate perception among the teachers is at high category (54.84%) and the majority of career planning is in high category too (51.61%). Based on the research result it can be concluded that there is a significant positive relationship between perceptions of organizational climate with career planning on the teacher, which means that the higher the perception of the organizational climate, the higher the teachers career planning.Keywords: perception of organizational climate, career planning